2019
DOI: 10.3748/wjg.v25.i29.3956
|View full text |Cite
|
Sign up to set email alerts
|

Berberine prevents stress-induced gut inflammation and visceral hypersensitivity and reduces intestinal motility in rats

Abstract: BACKGROUND Irritable bowel syndrome (IBS) is a common chronic non-organic disease of the digestive system. Berberine (BBR) has been used to treat patients with IBS, but the underlying therapeutic mechanism is little understood. We believe that BBR achieves its therapeutic effect on IBS by preventing stress intestinal inflammation and visceral hypersensitivity and reducing bowel motility. AIM To test the hypothesis that BBR achieves its therapeutic effect on IBS by preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…The reason for these targeted reductions is likely multi-layered. Psychological stress increases gut motility 84,85 , which may increase shear stress on mucosal-adhered microbial groups. In addition, given the fact that the microbiota exist in climax communities, alterations in mucosal immune function, nutrient availability, or epithelial barrier stability could all have drastic effects on microbiome structure 86,87 .…”
Section: Discussionmentioning
confidence: 99%
“…The reason for these targeted reductions is likely multi-layered. Psychological stress increases gut motility 84,85 , which may increase shear stress on mucosal-adhered microbial groups. In addition, given the fact that the microbiota exist in climax communities, alterations in mucosal immune function, nutrient availability, or epithelial barrier stability could all have drastic effects on microbiome structure 86,87 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that BBH has potential anti-inflammatory, antibacterial, analgesic, and antidiarrheal effects and a wide range of biological activities, especially in regulating the release of some neurotransmitters, which are involved in the pathological process of various neurological diseases. A recent study ( Yu et al, 2019 ) has shown that intestinal immune disorders are closely related to the pathogenesis of IBS. Cytokines are a part of intestinal immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for these targeted reductions is likely multi-layered. Psychological stress increases gut motility 82,83 , which may increase shear stress on mucosal-adhered microbial groups. In addition, given the fact that the microbiota exist in climax communities, alterations in mucosal immune function, nutrient availability, or epithelial barrier stability could all have drastic effects on microbiome structure 84,85 .…”
Section: Discussionmentioning
confidence: 99%